Chemical composition, fatty acid content and phenolics (bioactive) compound on linseed (Linum usitatissimum L.) harvested at six phenological stages of growth - Re G.A.; Sassu M.; Sulas L. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Linum usitatissimum L. is an annual dicotyledonous multipurpose crop grown either for fibre (fibre flax) or seed (linseed, oil seed flax or flax seed). Linseed straw can be exploited as source of roughage and although at the late stages is very fibrous, at the early stages, can be very nutritious, comparable to canola hay. Linseed and grass are the most important n-3 fatty acid sources for ruminants. Linoleic acid (LA, 18:2n-6) and α-linolenic acid (ALA, 18:2n-3) are both available in linseed. Plant secondary metabolites have attracted interest as potential antioxidants for both inhibiting deterioration of foodstuffs and for providing beneficial metabolic effects in animals. Evaluation of quality of linseed biomass, as an important source of precursors of fatty acids, and its chemical composition (total polyphenols, flavonoids and condensed tannins) at different morphological stages, was the first aim of this work.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)